HUBUNGAN PARENT ATTACHMENT DAN DUKUNGAN TEMAN SEBAYA DENGAN KECERDASAN EMOSIONAL REMAJA - Aulia Nurfadilah; Ika Nurfajriyani; Eva Riantika Ratna Palupi (Jurnal Keperawatan Jiwa, 2026)
Emotional intelligence factors consist of, the family environment, which is the main foundation of emotional education (parent attachment) and the non-family environment, namely social interactions other than with parents (peer support). The aim is to determine the relationship between parent attachment and peer support with adolescent emotional intelligence. The study used a correlational quantitative design with a cross-sectional approach. A sample of 90 students of SMPN 6 Subang was selected using stratified random sampling technique. Data were collected using the Inventory of Parent and Peer Attachment (IPPA), Peer Support Questionnaire (PSQ), and Trait Emotional Intelligence Questionnaire-Adolescent Short Form (TEIQue-ASF) questionnaires. Data analysis used was univariate and bivariate analysis using the Spearman rank statistical test. The results showed that most felt moderate parent attachment as many as 51 people (56.7%), and adolescents with peer support as many as 60 people (66.7%), and most adolescents had high emotional intelligence as many as 69 people (76.7%). There is a relationship between parent attachment and adolescent emotional intelligence with a value of ρ value = 0.000 < α = 0.05 with a value of r = 0.487. There is a relationship between peer support and adolescent emotional intelligence with a value of ρ value = 0.013 < α = 0.05 with a value of r = 0.262. Adolescents who have good parent attachment and peer support will be able to influence emotional intelligence.